Fabrication, microstructure and spectroscopic properties of Yb:Lu2O3 transparent ceramics from co-precipitated nanopowders. Issue 10 (July 2018) - Liu, Qiang; Li, Jinbang; Dai, Jiawei; Hu, Zewang; Chen, Cong; Chen, Xiaopu; Feng, Yagang; Li, Jiang
Abstract: Ytterbium doped lutetium oxide (Yb:Lu2 O3 ) transparent ceramics were fabricated by vacuum sintering combined with hot isostatic pressing (HIP) of the powders synthesized by the co-precipitation method. The effects of calcination temperature on the composition and morphology of the powders were investigated. Fine and well dispersed 5 at% Yb:Lu2 O3 powders with the mean particle size of 67 nm were obtained when calcined at 1100 °C for 4 h. Using the synthesized powders as starting material, we fabricated 5 at% Yb:Lu2 O3 ceramics by pre-sintering at different temperatures combined with HIP post-treatment. The influence of pre-sintering temperature on the densities, microstructures and optical quality of the 5 at% Yb:Lu2 O3 ceramics was studied. The ceramic sample pre-sintered at 1500 °C for 2 h with HIP post-treating at 1700 °C for 8 h has the highest in-line transmittance of 78.2% at 1100 nm and the average grain size of 2.6 µm. In addition, the absorption and emission cross sections of the 5 at% Yb:Lu2 O3 ceramics were also calculated.